2012
DOI: 10.3389/fphys.2012.00012
|View full text |Cite
|
Sign up to set email alerts
|

Biological Significance of Local TGF-β Activation in Liver Diseases

Abstract: The cytokine transforming growth factor-β (TGF-β) plays a pivotal role in a diverse range of cellular responses, including cell proliferation, apoptosis, differentiation, migration, adhesion, angiogenesis, stimulation of extracellular matrix (ECM) synthesis, and downregulation of ECM degradation. TGF-β and its receptors are ubiquitously expressed by most cell types and tissues in vivo. In intact adult tissues and organs, TGF-β is secreted in a biologically inactive (latent) form associated in a non-covalent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
85
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 137 publications
(173 reference statements)
1
85
1
Order By: Relevance
“…Second, there are many active binding sites in ECM secreted by cells for entrapment of various growth factors and calcium. For example, ECM component heparin sulfate proteoglycans have specific binding for bFGF, fibronectin specifically binds TGF-β26,27 . These growth factors play important roles in major…”
mentioning
confidence: 99%
“…Second, there are many active binding sites in ECM secreted by cells for entrapment of various growth factors and calcium. For example, ECM component heparin sulfate proteoglycans have specific binding for bFGF, fibronectin specifically binds TGF-β26,27 . These growth factors play important roles in major…”
mentioning
confidence: 99%
“…Cytokines, including transforming growth factor-beta 1 (TGFb1), platelet-derived growth factor (PDGF) and endothelial growth factor (EGF) induce the activated hepatic stellate cells to transform into myofibroblasts, [112][113][114][115] and interventions that inhibit the production of these cytokines may limit this transformation and reduce collagen production. Similarly, angiotensin II is secreted by hepatic stellate cells, and it induces their proliferation and the production of extracellular matrix.…”
Section: -111mentioning
confidence: 99%
“…This activated TβRI kinase phosphorylates Smad2 or Smad3, which subsequently form a complex with Smad4 and migrate to the nucleus to regulate expression of target genes, including collagens (Bauer and Schuppan, 2001;Zong et al, 2012). In the process of hepatic fibrosis, TGFβ is the main mediator of fibrogenesis, which can promote activation of HSCs and induce sustained production of ECM components (Friedman, 2000;Pinzani and Marra, 2001;Bataller and Brenner, 2005;Moreira, 2007;Hayashi and Sakai, 2012). Our study confirmed that HBx protein upregulated the mRNA and protein expression of TGFβ1 in HSCs, leading to activation of HSCs and increased expression of Col I (Kisseleva and Brenner, 2007).…”
Section: Effects Of Hbx On Hscsmentioning
confidence: 99%